Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2004
DOI: 10.1369/jhc.4a6279.2004
|View full text |Cite
|
Sign up to set email alerts
|

Corticotropin-releasing Factor 2 Receptor Localization in Skeletal Muscle

Abstract: Our objective in this study was to localize the corticotropin-releasing factor 2 receptor (CRF2R) in rodent and human skeletal muscle. We found CRF2R protein to be abundant in neural tissues in skeletal muscle, including large nerve fibers and bundles, neural tissue associated with mechanoreceptors, muscle spindles, and the Golgi tendon organ. CRF2R protein was also abundant in blood vessels in skeletal muscle. CRF2R protein was also observed, although with less abundance, in the endo/perimysial regions in ske… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
7
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 41 publications
(6 reference statements)
2
7
0
Order By: Relevance
“…This observation agrees with previous studies showing that administration of urocortin II (a CRF2R agonist) resulted in an increase in muscle mass in non‐atrophying muscles 17. Samuelsson et al33 showed that CRF2R in skeletal muscle was localized to neural structures, blood vessels, myotendinous junctions, and endomysial/perimysial spaces. Expression of CRF2R in skeletal muscle myocytes was not observed.…”
Section: Discussionsupporting
confidence: 91%
“…This observation agrees with previous studies showing that administration of urocortin II (a CRF2R agonist) resulted in an increase in muscle mass in non‐atrophying muscles 17. Samuelsson et al33 showed that CRF2R in skeletal muscle was localized to neural structures, blood vessels, myotendinous junctions, and endomysial/perimysial spaces. Expression of CRF2R in skeletal muscle myocytes was not observed.…”
Section: Discussionsupporting
confidence: 91%
“…In the present study we demonstrated, using specific mCRFR2 RNase protection assays, RT-PCR, and DNA sequencing, that adult SM tissue expresses CRFR2␤, but not the CRFR1, transcripts. Previous reports showed CRFR2␤ expression in SM to be localized in neural structures, blood vessels, myotendinous junctions, and endomysial/ perimysial spaces, but not in myocytes (45).…”
Section: Discussionmentioning
confidence: 82%
“…17 The CRF2R protein is localized in neuromuscular and myotendinous junctions as well as in endomysium and perimysium surrounding muscle fibers in rats, mice, and humans; however, expression was not observed in myocytes. 31 Blood vessels have also been shown to express the CRF2R protein. 31 Recently, it was shown that sauvagine, a nonselective CRFR agonist, completely inhibited muscle atrophy in casted CRF1R knockout mice.…”
mentioning
confidence: 99%
“…31 Blood vessels have also been shown to express the CRF2R protein. 31 Recently, it was shown that sauvagine, a nonselective CRFR agonist, completely inhibited muscle atrophy in casted CRF1R knockout mice. 17 However, the same treatment with noncasted mice had no significant effect on muscle mass.…”
mentioning
confidence: 99%